(3YfbhO GdRhGgQs - (3Ydj Hf eMeO GdWhSj GdHJGQcGfj, YdGA GdOjf,J (B877 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf ef GdYdhe def jbUO fXe YbO ef GdLhGgQ s
(3BNQgG (B:s
(3dYOe GfOQGLgG ajeG JhLgfG Edjg Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B9 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B185s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1174s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUQas